2009
DOI: 10.1007/s11814-009-0225-4
|View full text |Cite
|
Sign up to set email alerts
|

Purification and partial characterization of milk-clotting enzyme extracted from glutinous rice wine mash liquor

Abstract: Glutinous rice wine mash liquor is a traditional food of south of China and its ability to coagulate the milk has been proved. The aim of this work was to extract milk-clotting enzyme from glutinous rice wine mash liquor. A partial purified extract of enzyme was obtained by fractional precipitation with (NH 4 ) 2 SO 4 . The fractions obtained by precipitation, 40-90% possessed the milk-clotting activity (MCA) (145.72 U/mg). The 40-90% (NH 4 ) 2 SO 4 fraction was further purified by sephadex G-100 and DEAE-seph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
1

Year Published

2010
2010
2015
2015

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 36 publications
2
12
1
Order By: Relevance
“…In contrast, Mn 2+ had a significant stimulatory effect on milkclotting activity, whereas 1 mM Li + and 1 mM Mg 2+ promoted the activity slightly, but had no effect when present at concentrations of only 5 mM or 10 mM. These results were similar to those reported by Wang et al [23], who reported that Na + and K + inhibited the enzyme activity in glutinous rice wine mash liquor. In contrast, Na + and K + had no effect on the activity of milk-clotting enzyme from Bacillus polymyxa B-17 [31].…”
Section: Effect Of the Concentration Of Caclsupporting
confidence: 89%
See 1 more Smart Citation
“…In contrast, Mn 2+ had a significant stimulatory effect on milkclotting activity, whereas 1 mM Li + and 1 mM Mg 2+ promoted the activity slightly, but had no effect when present at concentrations of only 5 mM or 10 mM. These results were similar to those reported by Wang et al [23], who reported that Na + and K + inhibited the enzyme activity in glutinous rice wine mash liquor. In contrast, Na + and K + had no effect on the activity of milk-clotting enzyme from Bacillus polymyxa B-17 [31].…”
Section: Effect Of the Concentration Of Caclsupporting
confidence: 89%
“…2(b)). This result was similar to what is reported for the milk-clotting enzymes from Mucor miehei [22], Rhizopus oryzae [1] and glutinous rice wine mash liquor [23]. Like calf rennet, the purified enzyme from B. amyloliquefaciens D4 had a higher level of milk-clotting activity in the acidic range.…”
Section: Effects Of Temperature and Ph On Enzyme Activity And Stabilitysupporting
confidence: 88%
“…However, this method is ethically arguable and has low productivity. Thus, research has focused on the identification of alternative milk-clotting enzymes (MCEs) among animals, plants and microorganisms as calf rennet substitutes [2][3][4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Wang et al . () obtained a rennet‐like enzyme from glutinous rice wine mash liquor with a molecular weight of 36.0 kDa and they concluded that the enzyme was probably produced by moulds from the rice starter. Whether the MCE in this study was produced by molds present in the rice starter during glutinous rice fermentation needs to be further confirmed.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, genetically engineered enzymes (Vallejo et al 2012) have been explored. However, currently available MCEs still cannot meet the increasing worldwide demand for cheese production and many researchers continue to search for different sources of MCEs, including those produced by rice fermentation (Su et al 2007;Wang et al 2009).…”
Section: Introductionmentioning
confidence: 99%